Prospects for a transit regime on energy in the WTO - Ugaz, Pamela (Pontificia Universidad Católica del Perú. Fondo Editorial, 2011)
ndoubtedly trade in energy resources such as oil and gas represents a significant part of world trade flows. For instance, fuels alone represented 77% of the world natural resources exports (USD 2.9 trillion) in 2008. Its relevance will increase in the coming years driven chiefly by emerging economies. Indeed, the International Energy Agency (IEA) projects that oil demand will increase 1% per year, while gas demand 1.5% per year by 2030.
Keywords: Estudios internacionales; https://purl.org/pe-repo/ocde/ford#5.09.01